Linking trust and collaboration in project teams to project management success. Issue 2 (16th April 2018) - Bond-Barnard, Taryn Jane; Fletcher, Lizelle; Steyn, Herman
Abstract : Purpose: The purpose of this paper is to emphasise the importance of high levels of trust and collaboration for increasing the likelihood of project management (PM) success. However, the link between these three constructs remains unclear. Design/methodology/approach: In this study, the authors use structural equation modelling (SEM) based on the findings from an international survey of 151 project practitioners to demonstrate the significance of project team trust and collaboration for increasing the likelihood of PM success. Findings: The results indicate that PM success becomes more likely as the degree of collaboration improves which, in turn, is influenced by an increase in the level of trust between team members. The two factors of PM success are project performance and knowledge integration and innovation. The six factors of the degree of collaboration that were studied are physical proximity, commitment, conflict, coordination, relationships and incentives. The three factors of the level of trust investigated are expectations, knowledge exchange and imported trust. Practical implications: The results of the study are expected to provide insight for project practitioners to increase the likelihood of PM success by taking cognisance of the factors that influence collaboration and trust. The results of the study may also provide insight into teaching and learning in tertiary education, in terms of professionalism and integrity issues. Originality/value: This paper presents a new perspective for investigating PM success. SEM techniques are used to determine the likelihood of PM success by promoting trust and collaboration in the project team. This unique approach highlights the "human factors" that influence perceived PM success which should benefit both researchers and practitioners.